Development of Experimental Bag Media in the Subject of Science and Technology in the Independent Curriculum to Increase Students Understanding - Rahmaningrum, Maulia Zulfa; Fauziah, Giska Enny (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The purpose of this research is to improve the quality of IPAS learning, which has been less interesting and difficult to understand because it only relies on LKS. The experimental bag was created by researcher as a learning tool that helps students, helps teachers, and improves learning outcomes. Analysis, design, development, implementation, and evaluation are all parts of the Research & Development (R&D) method with the ADDIE development model. Design experts, material experts, and learning experts validated 97%, 92%, and 98% respectively. N-Gain analysis in the medium category (0.5) showed the effectiveness of the media, and the pilot test showed an average result of 99% in the small group and 101% in the large group. The results showed that the experimental bag can help students understand IPAS lessons in grade V.